2011
DOI: 10.1080/09649069.2011.632884
|View full text |Cite
|
Sign up to set email alerts
|

Legislative aspirations and social realities: empirical reflections on Australia's 2006 family law reforms

Abstract: The Australian government has recently introduced a Bill into Parliament that is intended to improve the way concerns about family violence and child abuse are dealt with in the context of post-separation parenting disputes. The move follows recent reports examining the impact of significant reforms to the family law system introduced in 2006. Motivated by a desire to ensure that children maintain involvement with both parents after separation and to place greater emphasis on non-court-based dispute resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…The agreement rate reported in this study (66%) is higher than earlier reports of agreement in Australian FDR (Kaspiew et al, 2009; Qu, 2019), though in keeping with studies of mediation elsewhere (Emery, 2012; Moloney et al, 2013). The agreement rate was lower among ambivalent participants (58%).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The agreement rate reported in this study (66%) is higher than earlier reports of agreement in Australian FDR (Kaspiew et al, 2009; Qu, 2019), though in keeping with studies of mediation elsewhere (Emery, 2012; Moloney et al, 2013). The agreement rate was lower among ambivalent participants (58%).…”
Section: Discussionsupporting
confidence: 76%
“…5 Studies from California, where mediation has been mandatory for several decades, provided cause for optimism in reporting majority agreement rates and strong client satisfaction (Depner et al, 1992;Kelly, 2004;Kelly & Duryee, 1992). 6 These statistics are not comparable for a number of reasons, including that the random sample surveys did not allow for partial agreements, and count respondents whose co-parent refused to participate in FDR in the denominator, or total of those who attempted FDR (Kaspiew et al, 2009;Moloney et al, 2013). This is an important difference, since as many as half of all FDR cases initiated do not progress to joint mediation because the respondent co-parent declines to participate (Morris et al, 2016).…”
Section: Funding Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are scenarios that are exempted to such process such as family violence or child abuse. An evaluation conducted found that one quarter of cases are successfully screened-out or excluded of family mediation because of these situations (Kaspiew et al, 2009).…”
Section: Compulsory Family Mediation Advantages and Limitationmentioning
confidence: 99%